PENGARUH MOTIVASI , DISIPLIN DAN KOMPENSASI TERHADAPKINERJA KARYAWAN DI PT GRAHA DWI PERKASA - Firwish, Sammy (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
In the world which everything is all-tech world, can’t away from Electrical. More electrical devices needed by humans and more new electrical devices would be created by humans to helping humans. Along with the rapid pace of the business world, especially in the electrical field to be able to survive every company should pay attention to the smooth company management, especially employee performance. PT Graha Dwi Perkasa still has problems is employees come late for work,lacking enthusiasm in working so that work is  delayed. The purposed of this study was to determined the effect from independent variables to the dependent variables. Writer using this type of research is quantitative research. Non-probability sampling method is used to process data and data collection techniques used saturated samples that distribute all questionnaires to 114 PT Graha Dwi Perkasa’s empolyees. Analysis technique using by writer is multiple linear regression and support of SPSS software version21. Results of T test showing us the t-value of the three variables is higher than the value of t table. So it can be concluded the results of the analysis motivation,discipline,and compensation variables simultaneously have a positive and significant effect on employee performance at PT Graha Dwi Perkasa.